A Study of Syntactic and Semantic Artifacts and its Application to Lambda Definability, Strong Normalization, and Weak Normalization in the Presence of... - Munk, Johan (BRICS Report Series, 2008)
Church’s lambda-calculus underlies the syntax (i.e., the form) and the semantics (i.e., the meaning) of functional programs. This thesis is dedicated to studying man-made constructs (i.e., artifacts) in the lambda calculus. For example, one puts the expressive power of the lambda calculus to the test in the area of lambda definability. In this area, we present a course-of-value representation bridging Church numerals and Scott numerals. We then turn to weak and strong normalization using Danvy et al.’s syntactic and functional correspondences. We give a new account of Felleisen and Hieb’s syntactic theory of state, and of abstract machines for strong normalization due to Curien, Crégut, Lescanne, and Kluge.